2019
DOI: 10.1111/bju.14961
|View full text |Cite
|
Sign up to set email alerts
|

The risk of developing cardiovascular disease is increased for patients with prostate cancer who are pharmaceutically treated for depression

Abstract: Objective To examine the associations between pharmaceutically treated anxiety and depression and incident cardiovascular disease (CVD) among 1‐year prostate cancer survivors. Patients and methods A registry‐based cohort study design was used to describe the risk of incident CVD in adult 1‐year prostate cancer survivors without a history of CVD. Patients with prostate cancer diagnosed between 1999 and 2011 were selected from the Netherlands Cancer Registry. Drug dispenses were retrieved from the PHARMO Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…More and more evidence suggested that cancer patients tend to have an increased risk of depressive symptoms which is related to poor treatment adherence, 1,2 as well as a high risk of cancer-related complications, such as cardiovascular diseases (CVDs) and all-cause mortality. [3][4][5][6] Patients in the cancer stage can intensify the symptoms of depression. A study pointed out that cancer-related depression risk factors include diagnosed cancer, poor pain control, cancer progression, physical damage or others.…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidence suggested that cancer patients tend to have an increased risk of depressive symptoms which is related to poor treatment adherence, 1,2 as well as a high risk of cancer-related complications, such as cardiovascular diseases (CVDs) and all-cause mortality. [3][4][5][6] Patients in the cancer stage can intensify the symptoms of depression. A study pointed out that cancer-related depression risk factors include diagnosed cancer, poor pain control, cancer progression, physical damage or others.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome and relevant cardiometabolic disorders, which are fully established as key risk factors for most CVDs, have been recently reported to play an important role in the pathogenesis of major prostate diseases (BPH and PCa) ( 17 , 19 , 26 29 ), highlighting an increased burden of prostate diseases coexisting with CVD in actual clinical settings. Epidemiological studies have reported that CVD is prevalent among patients with LUTS (primarily caused by BPH) or PCa ( 7 , 30 32 ). Furthermore, some PCa medications, including ADT (androgen deprivation therapy), have a potency that adversely affects the cardiometabolic status and increases the risk for cardiovascular complications ( 33 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the risk of developing AF is increased for patients with cancer due to shared risk factors, treatments, and disease itself [ 50 ].…”
Section: Mechanisms Of Increased Af and Atrial Cardiomyopathy In Cmentioning
confidence: 99%